Early Cretaceous to Middle Eocene Magmatic Evolution of Eastern Pontides: Zircon U-Pb Ages and Hf Isotopes, and Geochemical and Sr-Nd Isotopic Constraints from Multiphase Granitoids, NE Turkey - Sar, Abdullah; Kurum, Sevcan; Bingol, Ahmet Feyzi (China Univ Geosciences, Wuhan, 2023)
The Eastern Pontides orogenic belt (EPOB) represents a significant segment of the Alpine-Himalayan orogenic belt that evolved from the Paleozoic to Cenozoic periods. Here we report new zircon U-Pb ages, together with Lu-Hf isotopes, and whole-rock geochemical and Sr-Nd isotopic analyses of plutonic rocks from EPOB, northeastern Turkey. Our aim is to interpret magmatic evolution in which the granitoids formed. Zircon U-Pb dating of six samples yielded crystallization ages of similar to 134, similar to 82, similar to 39 Ma, respectively. They show a wide range of Sr-87/Sr-86((i)) (0.703 9-0.710 9), and epsilon(Nd)(t) values varying from -9 to +4.6, yielding model ages (T-DM) from 520 to 1 623 Ma, suggesting a heterogeneous magma source. Dated zircons show exlusively positive epsilon(Hf)(t) values (+12.4 to +1.4), yielding model ages (T-DM) from 352 to 1 059 Ma, implying that they are most likely derived from a juvenile lower crust rather than the mature continental crust. In this study, we suggested that the northward subduction of the Neo-Tethyan oceanic slab began from the Early Cretaceous and resulted in the Late Cretaceous magmatism. Moreover, the Middle Eocene magmatism in the EPOB was related to the collision of the Anatolide Taurid Platform (ATP) with the Pontides.
Keywords: zircon U-Pb ages; Hf isotope; Sr-Nd isotope; Cretaceous to Eocene Magmatism; Eastern Pontides; geochemistry